Reduced Regional Cerebral Blood Flow in Patients with Heart Failure - Roy, Bhaswati (Eur J Heart Fail, 2017)
AIM: Heart failure (HF) patients show significant lateralized neural injury, accompanied by autonomic, mood, and cognitive deficits. Both gray and white matter damage appears, and likely develops from altered cerebral blood flow (CBF), a consequence of impaired cardiac output. However, the distribution of regional CBF changes in HF patients is unknown, but is an issue in determining mechanisms of neural injury. Our aim was to examine regional CBF changes in HF over control subjects using non-invasive pseudo-continuous arterial spin labeling (pCASL) procedures. METHODS AND RESULTS: We collected pCASL data from 19 HF (age, 55.5±9.1 years; body-mass-index, 27.7±5.3 kg/m(2); 13 male) and 29 control subjects (51.4±5.3 years; 25.7±3.6 kg/m(2); 18 male), using a 3.0-Tesla-MRI scanner. Whole-brain CBF maps were calculated, normalized to a common space, smoothed, and compared between groups using ANCOVA (covariates; age, gender, and gray matter volume). Reduced CBF appeared in multiple sites in HF over controls, with principally-lateralized lower flow in temporal, parietal, and occipital regions. Areas with decreased CBF included the bilateral pre-frontal, frontal, temporal and occipital cortex, thalamus, cerebellum, corona radiate, corpus callosum, hippocampus, and amygdala. CONCLUSION: HF subjects showed lower, and largely lateralized, CBF in multiple autonomic, mood, and cognitive regulatory sites. The reduced CBF likely contributes to the lateralized brain injury, leading to autonomic and neuropsychological deficits found in the condition.